Chains of Love? Global Production and the Firm‐Level Diffusion of Labor Standards. Issue 3 (13th June 2018) - Malesky, Edmund J.; Mosley, Layna
Abstract: Under what conditions does the global economy serve as a means for the diffusion of labor standards and practices? We anticipate variation among internationally engaged firms in their propensity to improve labor standards. Upgrading is most likely when a firm's products exhibit significant cross‐market differences in markups, making accessing high‐standards overseas markets particularly profitable. Additionally, upgrading is more likely when lead firms attach a high salience to labor standards. Therefore, while participation in global production induces "trading up" behaviors among firms overall, the effect strength varies across industries. We test our expectations via a survey experiment, which queries foreign firms operating in Vietnam about their willingness to invest in labor‐related upgrading. We find strong evidence for the effect of markups on upgrading choices and suggestive evidence for the saliency mechanism.